Intractable Vaginismus – A New Approach of Management by Incision of Spasmodic Perivaginal Muscles and Resurfacing with Labia Minoraflaps - Prakash , Vishwa; Garg , Neeta (Advancement and New Understanding in Medical Science Vol. 9, 2024)
Introduction: Vaginismus is defined as recurrent or persistent involuntary spasm of the musculature of the lower third of the vagina, which interferes with coitus resulting in matrimonial disharmony. Vaginismus is believed to be a psycho-physiologic disorder due to fear from actual or imagined negative experiences with penetration. There are many methods described for the management of the condition. But most of times all methods fail to treat such patients. We have developed a newer approach for management of this condition in which spasmodic muscles are incised and resultant defect is resurfaced with Labia Minora Flaps. Materials and Methods: We have treated fourteen females who were married more than 5 years before and had undergone all types of treatment without success. Patients were operated in general anaesthesia without muscle relaxation. The peri-vaginal examination was done when a severe grip on the examining finger was felt. The mucosa was incised at the rim at 8 and 4’O clock about 2 cm long extending from vaginal mucosa to vestibular mucosa exposing the peri-vaginal muscles which were incised till the constriction ring disappeared. Results: All of the females could initiate sexual intercourse within 3 weeks of surgery. Conclusion: Incision of spasmodic muscles and resurfacing with labia minora flaps is one of good option if other treatment had failed, for management of vaginismus.